PENGEMBANGAN MAKANAN LOKAL MEGONO LAKTAGENIK UNTUK MENINGKATKAN PRODUKSI AIR SUSU IBU DAN MEMACU PERTUMBUHAN BAYI - Indar Widowati; Hartati Hartati; Zaenal Amirudin (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2019)
This researched aims to: 1) Develop local food potentials into innovative product of lactagenic megono food, 2) Analyzed the nutritional content of lactagenic megono product,3) Analyzed the influence of lactagenic megono on increasing breast milk production and infant growth. Methods of this researched include: 1) Hedonic organoleptic perceptive test of three megono recipes derived from the community around Pekalongan. The selected product then tested proximate and intervention was conducted by lactating mothers. The result of hedonic organoleptic test proves that the selected product is A megono recipe, the value of taste attribute got 87, the aroma got 84, the texture attribute got 89 and the color attribute got 86. The proximate test shows that the water content is 79,98%, the ash content is 2,611%, the fat content is 1,653%, the protein level is 2,967, andthe carbohydrate level is 12,789%. The mean of infant weight in the control group increased until to 3 rd weeks by 19.17 grams, in the intervention group of 684.26 grams. The average increase of breast milk volume in the control group was 63.413 ml, in the intervention group of 221.413 ml. The result of Anova test no difference of infant weight in control group (? value equal to 0,949> 0,05), in group of intervention given by megono lactagenichas significant difference (? value equal to 0,048